Fundamentals for the Dimensioning and Optimization of Prestressed Segmented Girders for Application in Bridge Crane Systems - Oellerich, Jan (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2022)
Bridge cranes are widely used as discontinuous material handling systems in industrial environments. The so-called crane bridge plays a central role in the overall construction. With increasing span widths and load capacities, the dimensions of the crane bridge also increase. The core of this work is the design and optimization of a new type of bridge crane system, which consists of individual segments and is eccentrically pretensioned by a tensile member.